SYSTEMATIZATION OF ARCHAEOLOGICAL SIGHTS IN MYKOLAIV REGION’S TERRITORY IN 80’S OF 20TH CENTURY: PREREQUISITES, RESEARCH AND RESULTS (Південний архів (історичні науки), 2023)
Cultural heritage is one of the basic factors in historical memory`s formation about past of the region, which is of crucial importance for preservation of information about spiritual and materialmeans of previous generations. There are interpretation, reinterpretation for modernity by material immovable cultural heritage is occupied a special place in this context. It has a decisive influence on formation of historical and cultural portrait of state as a whole and the region in particular. There are history of itself region is inextricably linked with the question of researching the cultural attainment of the Mykolaiv Oblast. At one time with the socio-political events that shaped present face of the region, there was a study of its past, which defines the historical and cultural portrait of the city and the region, which runs through the entire chronological line with a red line and connects the various existing in these territories in separate historical periods of society and culture. Purpose of article is reveals the process of cultural heritage archaeological object`s systematization on territory of Mykolaiv Oblast in the 1980s; analyzing the legal act that became the logical conclusion of the systematization process; classify objects included in the state register by species characteristics, geographical location and dating. The emphasis is on analysis of normative reality process of formation relevant for this time, the coverage of scientific course and research works of archaeological expeditions that carried out activities on the territory of the Mykolaiv region in the specified period, and their role and significance for the state accounting of monuments of history and culture. The methodological basis of the article is an organic set of, on the one hand, the basic principles of research: historicism, objectivity, comprehensiveness, systematicity and continuity, and on the other hand, research methods and means of knowledge: source analysis and synthesis. Research results and conclusions. As a result of research, were analyzed the main stages of archaeological expeditions conducted by institutions and organizations – the Institute of Archeology of the Academy of Sciences of the Ukrainian SSR, the Mykolaiv Regional Museum of Local History, the Ukrainian Society for the Protection of Historical and Cultural Sights in the 1980s . One of the main results of monument protection activities is highlighted – a legal act that supplemented the State List of Historical and Cultural Monuments of the Mykolaiv Region with new archaeological objects, most of which were recorded and described precisely in the specified time period – the 80s 20th century. The named document – «O hosudarstvennoi okhrane pamiatnykov istorii i kultury» – was approved by the decision of the executive committee of the Mykolaiv Regional Council of People’s Deputies dated August 9, 1988 No. 216.
Keywords: protection of cultural heritage, archeology, heritage`s protection law, sight, archaeological exploration, local history